Physical education classes at university as a factor in the development of students’ speed and strength abilities - Grigan, S.A.; Ryzhkin, N.V.; Korobov, I.A.; Gvozdikova, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to investigate the effect of incorporating additional exercises into students’ training programme on the development of speed-strength abilities. Methods and structure of the study. The experiment involved 100 students from Don State Technical University aged between 17 and 22. The initial level of speed-strength exercises was assessed for the control and experimental groups of students. The following tests were used for this purpose: 100-metre sprint, long jump (from a standing start and from a running start), standing long jump, and shuttle run. Results and conclusions. Based on the theoretical and methodological research of other authors, a programme has been developed to improve students’ speed-strength abilities, which includes hopping from foot to foot along a gymnastics bench, jumping over an obstacle on both feet, skipping, jumping on the spot whilst throwing a weight from the chest, and shuttle runs. The results of applying this programme showed positive progress in the experimental group across all test exercises: from 2.9% to 7.5% over three months.